Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.aninu.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Priming of intestinal cytoprotective genes and antioxidant capacity by dietary phytogenic inclusion in broilers

Abstract: The potential of a phytogenic premix (PP) based on ginger, lemon balm, oregano and thyme to stimulate the expression of cytoprotective genes at the broiler gut level was evaluated in this study. In particular, the effects of PP inclusion levels on a selection of genes related to host protection against oxidation (catalase [ CAT ], superoxide dismutase 1 [ SOD1 ], glutathione peroxidase 2 [ GPX2 ], heme oxygenase 1 [ HMOX1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…However, chronic HS exposure increased SOD activity in the liver, while lipid peroxides were decreased ( Lin et al., 2000 ). In the intestine, components of the antioxidant system are upregulated by various dietary PFA in broilers, although the magnitude of these changes, as well as impact on overall growth seem to vary based on the PFA studied, dose, and other stress challenges ( Botsoglou et al., 2002 ; Luna et al., 2010 ; Paraskeuas et al., 2016 ; Paraskeuas et al., 2017 ; Mountzouris et al., 2020 ).
Figure 1 Effect of PFA supplementation on circulating antioxidant markers in HS broilers.
…”
Section: Results and Dicussionmentioning
confidence: 99%
“…However, chronic HS exposure increased SOD activity in the liver, while lipid peroxides were decreased ( Lin et al., 2000 ). In the intestine, components of the antioxidant system are upregulated by various dietary PFA in broilers, although the magnitude of these changes, as well as impact on overall growth seem to vary based on the PFA studied, dose, and other stress challenges ( Botsoglou et al., 2002 ; Luna et al., 2010 ; Paraskeuas et al., 2016 ; Paraskeuas et al., 2017 ; Mountzouris et al., 2020 ).
Figure 1 Effect of PFA supplementation on circulating antioxidant markers in HS broilers.
…”
Section: Results and Dicussionmentioning
confidence: 99%
“…Hsp70 expression leads to a significant increase in antioxidant enzymes and inhibits the production of lipid peroxidation. It has been shown that upregulated HSP70/90 prevents heat-stress-induced intestinal mucosa damage by enhancing antioxidant status [ 43 , 167 ]. Hosseindoust et al [ 168 ] reported that the level of HSP70 was significantly upregulated in different sections of the small intestine of chicken under acute heat stress.…”
Section: Cytoprotective Role Of Hsps Against Heat-stress-induced Imentioning
confidence: 99%
“…The antioxidant substances in the intestinal tract can eliminate the peroxide in the intestinal tract and protect the intestinal mucosa ( Lin et al., 2016 ; Qiu et al., 2020 ). Similarly, the gut antioxidant performance will influence the activity of digestive enzymes ( Long et al., 2020b ; Mountzouris et al., 2020 ). The antioxidant enzymes such as SOD and CAT are indispensable key factors against oxidative stress that have the capacity to decompose superoxide and eliminate free radicals by using a chain reaction mechanism ( Shirani et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%